2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332634
|View full text |Cite
|
Sign up to set email alerts
|

Radar cross section of human cardiopulmonary activity for recumbent subject

Abstract: The radar cross section (RCS) corresponding to human cardio-respiratory motion is measured for a subject in two different recumbent positions. Lying face-up (supine), the subject showed an RCS of 0.326 m(2). But when lying face-down (prone), the RCS increased to 2.9 m(2). This is the first reported RCS measurement corresponding to human cardio-respiratory motion. The results obtained in this experiment suggest modeling the upper part of the human body as a half-cylinder where the front body corresponds to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The choice of frequency also affects the Radar cross section of the target. It was shown in [6] that detection of physiological motion using 2.4 GHz provided a higher sensitivity to orientation whereas using 5.8 GHz provided higher displacement resolution. The use of radar systems with different frequencies allows more flexibility in determining and verifying the appropriate signal content.…”
Section: Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of frequency also affects the Radar cross section of the target. It was shown in [6] that detection of physiological motion using 2.4 GHz provided a higher sensitivity to orientation whereas using 5.8 GHz provided higher displacement resolution. The use of radar systems with different frequencies allows more flexibility in determining and verifying the appropriate signal content.…”
Section: Design Considerationsmentioning
confidence: 99%
“…4(b) with the 2.45GHz radar, a simple arc is formed due to the periodic motion. Analysis of the IQ signals in this case can be performed using a simple linear demodulation technique, and the measurement has higher sensitivity to the orientation of the body in practical subject measurements [6]. …”
Section: Measurementsmentioning
confidence: 99%
“…While many systems have been developed for this purpose, which frequencies to use and from which angle of incidence have not been given much attention. In 9 it was found that a person lying down has a larger radar cross section (RCS) of the cardiopulmonary activity from the back than from the front. In 10 the breathing cross section on a person lying down from various angles using an ultra wide band (UWB) radar with center frequency 750 MHz was calculated.…”
Section: Introductionmentioning
confidence: 98%
“…As part of the radar equation, is a necessary number for Signal to Noise Ratio (SNR) and detection computations and the understanding of radar signals in heartbeat and respiration monitoring. [4] and [5] measured the RCS of respiration. In [4], the human breathing cross section was investigated from various positions using an UWB impulse radar.…”
Section: Introductionmentioning
confidence: 99%
“…The reflection was reported to be strongest when the person was facing the receiving antenna. In [5], the RCS of respiration was computed using the phase changes in a Continous Wave (CW) Doppler radar recording of a breathing person. From the recordings, the amplitude of the reflections off the person was estimated.…”
Section: Introductionmentioning
confidence: 99%